2012
DOI: 10.1016/j.jviscsurg.2012.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Repeat hepatectomy for liver metastases from colorectal primary cancer: A review of the literature

Abstract: Repeat hepatectomy seems justified, since it may result in prolonged survival with acceptable rates of morbidity and mortality, results similar to those seen after initial hepatectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
18
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 51 publications
5
18
1
Order By: Relevance
“…Following a second hepatic resection, median survival was 42.0 months and 5-year survival was 32.6%. These outcomes are similar to other reports [85] and suggest that repeat hepatectomy is feasible and beneficial in select patients.…”
Section: Recurrent Hepatic Metastasessupporting
confidence: 91%
“…Following a second hepatic resection, median survival was 42.0 months and 5-year survival was 32.6%. These outcomes are similar to other reports [85] and suggest that repeat hepatectomy is feasible and beneficial in select patients.…”
Section: Recurrent Hepatic Metastasessupporting
confidence: 91%
“…Nevertheless, a few studies have reported actual 10-year follow-up which, unlike actuarial survival, provides not a statistical estimate but actual observations [2][3][4]. Despite the small number of patients, our single center study found a 10-year actual DFS of 19 % and a 10-year actual overall survival of 22 %, which is comparable to those reported by [9] reported that the results of repeat hepatectomy are similar to those of first surgery. In our study, 11 selected patients (13 %) underwent rehepatectomy and three of them survived for more than 10 years.…”
Section: Discussionsupporting
confidence: 75%
“…The characteristics of the CLM are summarized in Table 2. The mean size of metastases was 6±4 cm [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], and the mean number was two. According to subgroup analysis, segment I location was not significantly associated with a positive surgical margin.…”
Section: Characteristics Of Patients and Metastasesmentioning
confidence: 99%
“…This aspect is of paramount importance in presence of tumours next to or in contact with major vessels; in these cases, in absence of clear signs of vascular invasion at the IOUS, the vessel resection and consequent major liver resection should be avoided, offering with a parenchyma sparing policy lower post-operative morbidity and mortality. Moreover the avoidance of major hepatectomy allows the possibility of further repeated hepatectomies in patients with disease recurrence, those have shown similar morbidity and mortality compared to first hepatectomy [50].…”
Section: Echo-guided Liver Resectionmentioning
confidence: 99%